Religion, culture, and identity: the generational evolution of identification with Buddhism from the perspective of young Chinese Indonesians - Jingyi, Xie (International journal of children's spirituality, 2024)
This study aims to explore the generational shifts in identification with Buddhism from the perspective of young Chinese Indonesians. The study combines quantitative surveys and qualitative interviews to collect data from 257 respondents spanning three generations (grandparents, parents, and children) across 10 provinces in Indonesia. The findings indicate a general trend of generational decline in Identification with Buddhism among Chinese Indonesians. Identification with Buddhist symbols declines most rapidly, while recognition of Buddhist behavioural patterns shows the least decline. The alignment with Buddhist values and perceptions initially changes slowly but accelerates in decline over time. Additionally, there is a negative correlation between Buddhist identity and emotional engagement, reflecting complex intergenerational dynamics. The analysis also reveals significant effects of regional differences, community relationships, and familial occupational backgrounds on the decline in levels of Identification with Buddhism.